Fundamental of Entrepreneurship ENT300 : Polar Launderette / Adiba Adha Sadon ... [et al.] - Sadon, Adiba Adha; Mohd Yaacob, Mohd Izz Syahmi; Jeman, Noradriana; Ismail, Nursuhaidah (2014)
Polar Laundrette, differ from any laundry where you need to queue your item to be wash and dry. Our Laundrette emphasizes on speedy, washing method and cost effectives. With latest technology wash and dry washing machines we can ensure you that your time is not wasted washing for your clothes to be wash. We agreed that Mohd. Izz Syahmi B. Mohd Yacob is our general managers, Nursuhaidah Binti Ismail as our Administration Managers, Adiba Adha Binti Sadon as our Operational Managers, and again Mohd Izz Syahmi B. Mohd Yacob as Marketing Managers, and last but not least our Financial Managers, Noradriana Binti Jeman.